Persepsi Mahasiswa Universitas Islam Negeri Sumatera Utara Terhadap Akun @Tirtacipeng pada Aplikasi Tik Tok - Siti Nurhaliza Danti; Sori Monang; Abdul Karim Batubara (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2022)
This study aims to determine the perceptions and motives of students looking at the @tirtacipeng account on the Tik Tok application. The theory used in this study is the S-O-R Theory. The subjects of this study were IKOM-8 UINSU students. The research time is from July to August 2021. The method used in this research is the Qualitative Method with In-depth Interviews (in-depth interviews). Technical analysis used is descriptive qualitative analysis. The results of this study show that there are many similar opinions, some of the informants assess in terms of perceptions of the physical environment and social perceptions. In determining the resource persons, they prioritize the inspirational values of various aspects of the life of the informants. In addition, the criteria for selecting sources on the @tirtacipeng account on the Tik Tok application are open, i.e. various groups are possible to become sources and are basically designed in such a way as inspirational and useful posts. Some of the informants also considered the educational aspect to be more dominant and the @tirtacipeng account posting was on the media industry's Tik Tok application which aims to benefit informants. The motive that encourages students to view the @tirtacipeng account on the Tik Tok application is to obtain a variety of information of educational value as well as educational information from the reality of the public life of certain figures.